Developmental outcomes across foster care, adoption, and child welfare services: a mini review - Solerdelcoll, Mireia; Sugranyes, Gisela; Baeza, Inmaculada (Frontiers in Psychiatry, 2026)
Children entering foster care (FC), adoption, or child welfare services (CWS) frequently experience early adversity, placing them at increased risk across multiple developmental domains. A structured narrative search (2020–October 2025) identified 61 eligible studies, including 22 high-quality longitudinal, administrative, and review-based ‘core’ studies. Findings were synthesised across five predefined domains to provide comparative evidence on placement stability, psychological and behavioural health, educational attainment, physical and developmental health, and social relationships. Findings indicate that FC is most consistently associated with instability and cumulative disadvantage, including high rates of mental health problems, disrupted education, unmet health needs, and relational difficulties. Adoption generally provides greater permanence and more favourable outcomes, particularly when it occurs early, though adoption at later ages or following institutional care is often linked to enduring emotional, behavioural, and neurodevelopmental difficulties. Children who remain with their families under CWS support show highly variable trajectories, with positive outcomes when interventions are timely and sustained, but persistent difficulties when family adversity continues and systemic support is lacking. Across pathways, placement stability—conceptualised as both an outcome domain and a protective process—consistently emerges, alongside secure relationships, trauma-informed approaches, and coordinated support, as a critical factor safeguarding children’s developmental outcomes. However, the evidence base remains limited, with few longitudinal, intervention-driven, and culturally inclusive studies. Addressing these gaps is essential to advance policy and practice reforms that promote more responsive and coordinated systems of care, enabling children to build resilience and achieve long-term wellbeing.